UMP and UMW Collaboration Plant 2,000 Mangrove Trees in Cherating - Mimi Rabita, Abdul Wahit (2023)
CHERATING, 13 May 2023 - With the goal of planting 300,000 mangrove trees by 2023 as part of the UMW Green Shoots Initiative (UGS), the UMW Group continues its planting activities in Cherating, Kuantan.